Scintigraphie osseuse trois temps dans la caractérisation de l’ostéonécrose aseptique de la tête fémorale.: Three-stage bone scintigraphy in the characterization of aseptic osteonecrosis of the femoral head. - KI Thierry Romuald; DJIGO Salif; SOUGUE Charles; ZOUNGRANA Mamounata; KOKOU Adambounou; MBODJ Mamadou, (Journal Africain d Imagerie Médicale (J Afr Imag Méd) Journal Officiel de la Société de Radiologie d’Afrique Noire Francophone (SRANF), 2024)
Objective : Determine the role of three-step bone scintigraphy (BS) in the diagnosis of aseptic osteonecrosis of the femoral head (AOFH). Materials and Method : Retrospectively we collected 62 positive bone scans (BS+) at aseptic osteonecrosis of the femoral (AOFH). These BS+ were carried out at the Nuclear Medicine Department of CHU YO, from 2017 to 2022. A data collection form has been prepared. It made it possible to collect general data and the results of the bone scintigraphy. The descriptive study consisted of calculating the frequencies for the qualitative variables and the means for the quantitative variables. The three-step BS was performed in all patients after injection of 296 to 925 MBq of a diphosphonate derivative : hydroxy methylene diphosphonate (HMDP) labeled with technetium 99 m (Tc99m). Results : 62 patients were positive (BS +) in the aseptic avascular osteonecrosis of the femoral head scintigraphic research from 2016 to2021. Their average age is 35 ± 14.18 years with a clear female predominance (75.8%). The main etiology fremains sickle cell anemia. Hip pain with or without lameness indicated the realization of SO in 41.66% of cases. The twenty-five patients (40.3%) who had undergone CT of the affected hip were referred for confirmation of the diagnosis (n=4), preoperative workup (n=9), search for other foci (n=12). For the eleven patients with cancerous pathology, the diagnosis of AOFH was fortuitous after an BS performes as part of their extension workup. On the late scintigraphic images, type II involvement of GOLLSHALK was predominant, followed by type III then type I. There was no type IV involvement. Conclusion : BS is sensitive in the detection of aseptic avascular osteonecrosis of the femoral head before the onset of clinical symptoms and radiological translation. When MRI is available and not contraindicated, BS is the second-line modality. RÉSUMÉ  Objectifs. Déterminer la place de la scintigraphie osseuse 3 temps dans le diagnostic de l’ostéonécrose avasculaire de la tête fémorale (OATF). Matériels et Méthode. Nous avons colligé rétrospectivement 62 scintigraphies osseuses (SO+) mettant en évidence une OATF. Ces SO+ ont été réalisées au Service de Médecine Nucléaire du CHU YO de Ouagadougou, de 2017 à 2022. Un formulaire de recueil de données a permis de collecter les données générales et les résultats de la scintigraphie osseuse. L’étude descriptive consistait à calculer les fréquences pour les variables qualitatives et les moyennes pour les variables quantitatives. La SO en trois temps a été faite chez tous les patients après injection de 296 à 925 MBq d’un dérivé diphosphonate : l’hydroxy méthyléne diphosphonate (HMDP) marqué au technétium 99 m (Tc99m). Résultats. 62 patients ont présenté une SO+ à la recherche scintigraphique de l’OATF de 2016 à 2021. Leur âge moyen est de 35 ± 14,18 ans avec une nette prédominance féminine (75,8%). La principale étiologie retrouvée etait la drépanocytose. La douleur coxale avec ou sans boiterie a indiqué la réalisation de la SO dans 41,66 % des cas. Les vingt-cinq patients (40,3%) qui avaient bénéficié d’une TDM de la hanche concernée ont été adressés pour confirmation du diagnostic (n=4), bilan pré opératoire (n=9), recherche d’autres foyers (n=12). Pour les onze patients atteints de pathologie cancéreuse, le diagnostic d’OATF était fortuit au décours d’une SO réalisée dans le cadre de leur bilan d’extension. Sur les images scintigraphiques tardives, les atteintes de type II de GOLLSHALK étaient majoritaires, suivies des atteintes de type III puis de type I. Il n’y avait pas d’atteinte de type IV. Conclusion. La SO est efficace dans la caractérisation de l’OATF avant l’apparition de la symptomatologie clinique et de la traduction radiologique. Lorsque l’IRM est disponible et n’est pas contre indiquée, la SO est la modalité diagnostique à utiliser en deuxième intention.